Environmental literacy of high school students. (June 2020) - Prasetiyo,; Irawati, M H; Ibrohim,; Saptasari, M
Abstract: The goal of this research is to find out the environmental literacy of the tenth grade of Senior High School students. The aspects of environmental literacy presented include knowledge, cognitive skills, and attitudes towards the environment. Research applies descriptive methods. The results of the study showed that the average score of students' knowledge was 11.5 which was in the medium category, students' attitude towards environment was 28.5 which was considered as low category and cognitive skills which included issue identification was 5.4 and it was in the medium category, issues analysis with an average of 30.35 was in the low category and the student action plans with the highest percentage of 64.4% was in the form of reporting to the government and asking for a ban on land sales and there was 17.9% of students who did not have an action plan.